Multimodality Deep Phenotyping Methods to Assess Mechanisms of Poor Right Ventricular–Pulmonary Artery Coupling. Issue 4 (30th April 2022) - Raza, Farhan; Kozitza, Callyn; Lechuga, Chris; Seiter, Daniel; Corrado, Philip; Merchant, Mohammed; Dharmavaram, Naga; Korcarz, Claudia; Eldridge, Marlowe; Francois, Christopher; Wieben, Oliver; Chesler, Naomi
Abstract: Deep phenotyping of pulmonary hypertension (PH) with multimodal diagnostic exercise interventions can lead to early focused therapeutic interventions. Herein, we report methods to simultaneously assess pulmonary impedance, differential biventricular myocardial strain, and right ventricular:pulmonary arterial (RV:PA) uncoupling during exercise, which we pilot in subjects with suspected PH. As proof-of-concept, we show that four subjects with different diagnoses [pulmonary arterial hypertension (PAH); chronic thromboembolic disease (CTEPH); PH due to heart failure with preserved ejection fraction (PH-HFpEF); and noncardiac dyspnea (NCD)] have distinct patterns of response to exercise. RV:PA coupling assessment with exercise was highest-to-lowest in this order: PAH > CTEPH > PH-HFpEF > NCD. Input impedance (Z0 ) with exercise was highest in precapillary PH (PAH, CTEPH), followed by PH-HFpEF and NCD. Characteristic impedance (ZC ) tended to decline with exercise, except for the PH-HFpEF subject (initial Zc increase at moderate workload with subsequent decrease at higher workload with augmentation in cardiac output). Differential myocardial strain was normal in PAH, CTEPH, and NCD subjects and lower in the PH-HFpEF subject in the interventricular septum. The combination of these metrics allowed novel insights into mechanisms of RV:PA uncoupling. For example, while the PH-HFpEF subject had hemodynamics comparable to the NCD subject at rest, with exercise coupling dropped precipitously, which can be attributed (by decreased myocardial strain of interventricular septum) to poor support from the left ventricle (LV). We conclude that this deep phenotyping approach may distinguish afterload sensitive vs. LV-dependent mechanisms of RV:PA uncoupling in PH, which may lead to novel therapeutically relevant insights. Graphical Abstract: